Sejarah Perbandingan Manajemen Pendidikan - Retno Ambar Wati; Atik Likai Tanjua; Kristanti Olivia; Asiyah Asiyah (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This study aims to analyze the contribution of classical and modern management theories in establishing the foundations of educational management in Indonesia. The study focuses on Frederick W. Taylor's scientific management theory, Henri Fayol's administrative theory, Max Weber's bureaucracy theory, and Peter F. Drucker's modern management theory. The research method used is library research with a content analysis approach, which examines relevant literature in the form of books, journals, and articles. The results of the study show that Taylor emphasizes work efficiency through systematic procedures, Fayol emphasizes the importance of managerial functions (planning, organizing, directing, controlling), Weber emphasizes order and formal legitimacy through rational rules, while Drucker focuses more on achieving vision, innovation, and empowering people as knowledge workers. In general, the theories of Taylor, Fayol, and Weber provide a classical foundation for educational management with an orientation towards structure, efficiency, and rules, while Drucker provides a modern foundation that emphasizes flexibility, innovation, and social relevance. Thus, a combination of classical and modern theories can be used as a strategic basis to strengthen Indonesian educational management to be more adaptive in facing global challenges and the digital era.